Private regulation, public policy, and the perils of adverse ontological selection - Janina Grabs; Graeme Auld; Benjamin Cashore (Regulation & Governance, 2021)
What problems can private regulatory governance solve, and what role should public policy play? Despite access to the same empirical evidence, the current scholarship on private governance offers widely divergent answers to these questions. Through a critical review, this paper details five ontologically distinct academic logics – calculated strategic behavior; learning and experimentalist processes; political institutionalism; global value chain and convention theory; and neo-Gramscian accounts – that offer divergent conclusions based on the particular facets of private governance they illuminate, while ignoring those they obfuscate. In this crowded marketplace of ideas, scholars and practitioners are in danger of adverse ontological selection whereby certain approaches and insights are systematically ignored and certain problem conceptions are prioritized over others. As a corrective, we encourage scholars to make their assumptions explicit, and occasionally switch between logics, to better understand private governance's problem-solving potential and its interactions with public policy.
Keywords: 330; critical review; ontological influence; private regulatory governance; public policy; public–private interaction